Recognizing animal using interactive 3D animation / Ismalela Ismail - Ismail, Ismalela (Faculty of Computer and Mathematical Sciences, 2005)
Recently ICT is very important and fast growing. Therefore, a lot of educational aid which are related to computer technology becoming very popular among teacher and student. For example is education software. But the problems are most of the software are important fi"om oversea, especially for pre-school students. In addition, the Ministry of Education only provides the software for KBSM and KBSR. Therefore, developer take this opportimities to develop the software as an alternative for learning software industry in Malaysia, which use Bahasa Melayu as an interaction language. This project focused on pre-school student aged 5-6 years old. The topic selected re about animal. This software consists of interactive 3D animation. This approach is used to attract the student attention, indirectly. It can increase the skill of computer application of early stage. SDLC was chosen as the method of development because it is more structure and easy to understand. All the development process can be monitored clearly. In order to increase understand level of the student, this software was completed with exercises that support each subtopic. This software also included with kraoke session to attract the students in this learning process.